Habitat Loss Challenges the Conservation of Endemic Plants in Mining-Targeted Brazilian Mountains - Salles, Debora M; Carmo, Flávio F do; Jacobi, Claudia M (Environmental conservation, 2019)
Ironstone outcrop habitats harbour rare and endemic rupicolous plants. In southeast Brazil, they concentrate on mountaintops in the Iron Quadrangle (IQ), an intensively exploited iron ore reserve. To evaluate the current habitat availability of 32 plants endemic to canga (ironstone outcrops) and to support priority conservation areas and actions, we compared their functional connectivity in the IQ before (1960s) and after (2014) massive habitat loss to opencast mining. The Integral Index of Connectivity and associated metrics of habitat availability were used to evaluate present and past connectivity at a threshold distance of 500 m. The overall canga habitat loss up to 2014 was 50%. The historical configuration of 334 patches totalling 18 654 ha was already disconnected and the proportion of patches acting as relevant stepping stones was thus very low. Furthermore, in both the historical and current settings, the largest contribution to habitat availability came from ‘intrapatch connectivity’ (i.e., patch area), especially in the east sector. All the IQ canga endemics fall into the International Union for Conservation of Nature (IUCN) Critically Endangered category and require protection. The recommended strategy for their conservation is to protect large, preferably well-preserved ironstone patches. This measure will require finding the middle ground between economic development and conservation of natural heritage.